Where do we go from here? Method and pedagogy in language teaching - Penny Ur (ExELL (Explorations in English Language and Linguistics))
Language-teaching methods such as audio-lingualism or task-based instruction have been promoted at different times as the ‘best’ way to teach a foreign language. Each such method prescribes a set of learning procedures rooted in a particular theoretical conceptualization of the nature of language and language acquisition, based on linguistic and applied linguistics research. It is suggested in this article that the principles guiding teachers in selecting procedures should not be dictated by any particular method recommended by researchers or theoreticians, but should be rather defined as a pedagogy of language teaching, shaped by various general pedagogical – not only language-learning – considerations, as well as by local factors, and determined by the teacher her- or himself.